To be or not to be a rights holder: direct and indirect effects of perceived rights on psychological adjustment through group identification in care - Magalhães, E. (2017)
This study explores how young people in residential care perceive their rights and the relationship with their adjustment, through the role of group identification. Data from a non-random sample of young people (N = 356; aged 11-18 years) in Portuguese residential settings was analysed and a set of mediation effects was found. Findings revealed a set of mediation effects on the relationship between Participation and Protection and Positive Self and between Respectful system practices and behaviours and Emotional Distress, Anger Control and Antisocial Behaviour. Higher scores of these rights perceptions were associated with lower psychological problems, through the indirect effect of group identification (i.e., the sense of belonging to the group in residential care). These findings are discussed based on social and developmental insights together with empirical evidence on residential care. These results provided important practical implications in residential care, namely, assuring the young people's participation, the promotion of professional practices based on the respect for young people and their families, non-discriminatory behaviours and equal opportunities.